Evidence of Plasticity‐Driven Conductivity Drop in an Ultra‐Low‐k Dielectric Organosilicate Glass. (11th September 2022) - Rusinowicz, Morgan; Volpi, Fabien; Parry, Guillaume; Braccini, Muriel; Boujrouf, Chaymaa; Verdier, Marc
Abstract: Advanced devices (for microelectronics, energy storage, power sourcing) are complex architectures of metals and dielectrics subjected to harsh mechanical stresses. The functional reliability of the embedded dielectrics is driven by their ability to preserve their electrical properties (such as leakage and breakdown). Accordingly, understanding the interplay between the mechanical and electrical behaviors of dielectric films is critical to predict the lifetime of functional devices. In this study, the effect of plastic deformation on the electrical conduction of an ultra‐low‐k dielectric film is elucidated by combining in situ advanced experiments and finite element modeling. Experimentally, "electrical‐nanoindentation" tests emphasize the strong correlation between electrical and mechanical failures (leakage degradation, breakdown, plasticity, cracking). These experiments also reveal a counterintuitive electrical conduction drop under high mechanical stresses. This phenomenon is reproduced numerically by correcting the Poole–Frenkel conduction law with a strain‐dependent factor, and described analytically in terms of space‐charge build‐up induced by the trapping of holes at the mechanically generated defects. A threshold strain is identified as the keystone relating this strain‐dependent conduction to the current line distribution within the dielectric. This study provides a new understanding of the mechanical/electrical couplings in dielectrics, which opens promising insights into reliability issues for advanced devices. Abstract : The interplay between structural defects, induced by plastic deformation, and electrical conduction in an ultra‐low‐permittivity organosilicate glass is described. Thanks to an approach coupling in situ experiments with numerical/analytical modeling, a conductivity drop under high mechanical stresses can be fully explained. This new understanding of the mechanical/electrical coupling in dielectrics yields promising insights into reliability issues of advanced devices.